Comparison of Separation Control Mechanisms for Synthetic Jet and Plasma Actuators - Yoshiaki Abe; Taku Nonomura; Makoto Sato; Hikaru Aono; Kozo Fujii (Actuators, 2023)
This study numerically investigated the mechanisms of separation control using a synthetic jet (SJ) and plasma actuator (PA) around an NACA0015 airfoil at the chord Reynolds number of 63,000. Both SJ and PA were installed on the leading edge with the same order of input momentum (<semantics>Cμ=O(10−3</semantics>–<semantics>10−5)</semantics>) and the same actuation frequencies in <semantics>F+=1.0</semantics>–30. The momentum coefficient <semantics>Cμ</semantics> is defined as the normalized momentum introduced from the SJ or the PA, and <semantics>F+</semantics> stands for the actuation frequency normalized by the chord length and uniform velocity. A number of large-eddy simulations (LES) were conducted for the SJ and the PA, and the mechanisms were clarified in terms of the exchange of chordwise momentum with Reynolds shear stress and coherent vortex structures. First, four main differences in the induced flows of the SJ and the PA were clarified as follows: (A) wall-tangential velocity; (B) three-dimensional flow structures; (C) spatial locality; and (D) temporal fluctuation. Then, a common feature of flow control by the SJ and the PA was revealed: a lift-to-drag ratio was found to be better recovered in <semantics>F+=6.0</semantics>–20 than in other frequencies. Although there were differences in the induced flows, the phase decomposition of the flow fields identified common mechanisms that the turbulent component of the Reynolds shear stress mainly contributes to the exchange of the chordwise (streamwise) momentum; and the turbulent vortices are convected over the airfoil surface by the coherent spanwise vortices in the frequency of <semantics>F+</semantics>.